'Over to you': using a STAMP control structure analysis to probe deeper into the control of UK road safety at a municipal level – the case of Cambridgeshire. Issue 3 (4th March 2022) - Staton, Matt; Barnes, Jo; Morris, Andrew; Waterson, Patrick
Abstract: The UK has seen little progress in reducing road death over the last decade and as a result, the government has been criticised by industry stakeholders for a lack of leadership, including the removal of national targets in 2011 and the devolution of powers to a municipal level. The aim of this paper is to understand how decision-making at a municipal level takes place from a systems perspective, using the case study of Cambridgeshire. Actors involved were mapped using a STAMP control structure analysis and highlighted a key role for formal and informal partnerships between local and national government agencies and non-government organisations at the same level in the control structure. The changing international context of the model for the UK is also discussed in relation to the UK's withdrawal from the European Union and provides a useful tool for future analysis of its effect on policy and decision-making. Practitioner summary: This paper uses a STAMP control structure analysis to understand how decision-making at a municipal level takes place from a systems perspective, using the case study of Cambridgeshire. It highlights a key role for formal and informal partnerships between organisations at the same level in the control structure. Abbreviations: STAMP: System Theoretic Accident Model and Processes; STAMP-CAST: Systems-Theoretic Accident Model and Processes – Causal Analysis using Systems Theory; FRAM: Functional Resonance Analysis Method; HFACS: Human Factors Analysis and Classification Scheme; NGO: Non-Government organisation; iRAP: International Road Assessment Programme; EuroRAP: European Road Assessment Programme; NCAP: New Car Assessment Programme; CCG: Clinical Commissioning Group; GP: General Practitioner; PPE: Personal Protective Equipment; SD: standard deviation; Beds: Bedfordshire; Cambs: Cambridgeshire; Herts: Hertfordshire; Pboro: Peterborough.